Mind the gaps: age and cause specific mortality and life expectancy in the older population of South Korea and Japan - Myunggu Jung; Woorim Ko; William Muhwava; Yeohee Choi; Hanna Kim; Young Su Park; Gizachew Balew Jambere; Youngtae Cho (BMC, 2020)
Abstract Background Recent life expectancy gains in high-income Asia-pacific countries have been largely the result of postponement of death from non-communicable diseases in old age, causing rapid demographic ageing. This study compared and quantified age- and cause-specific contributions to changes in old-age life expectancy in two high-income Asia-pacific countries with ageing populations, South Korea and Japan. Methods This study used Pollard's actuarial method of decomposing life expectancy to compare age- and cause-specific contributions to changes in old-age life expectancy between South Korea and Japan during 1997 and 2017. Results South Korea experienced rapid population ageing, and the gaps in life expectancy at 60 years old between South Korea and Japan were reduced by 2.47 years during 1997 and 2017. Decomposition analysis showed that mortality reductions from non-communicable diseases in South Korea were the leading causes of death contributing to the decreased gaps in old-age life expectancy between the two countries. More specifically, mortality reductions from cardiovascular diseases (stroke, ischaemic and hypertensive heart disease) and cancers (stomach, liver, lung, pancreatic cancers) in South Korea contributed to the decreased gap by 1.34 and 0.41 years, respectively. However, increased mortality from Alzheimer and dementia, lower respiratory tract disease, self-harm and falls in South Korea widened the gaps by 0.41 years. Conclusions Age- and cause- specific contributions to changes in old-age life expectancy can differ between high-income Asia-pacific countries. Although the gaps in old-age life expectancy between high-income Asia-pacific countries are primarily attributed to mortality changes in non-communicable diseases, these countries should also identify potential emerging threats of communicable diseases and injuries along with demographic ageing in pursuit of healthy life years in old age.